Atheroprotective Reverse Cholesterol Transport Pathway Is Defective in Familial Hypercholesterolemia - Bellanger, Natacha; Orsoni, Alexina; Julia, Zélie; Fournier, Natalie; Frisdal, Eric; Duchene, Emilie; Bruckert, Eric; Carrie, Alain; Bonnefont-Rousselot, Dominique; Pirault, John; Saint-Charles, Flora; Chapman, M. John; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2011)
OBJECTIVE—Low high-density lipoprotein (HDL) cholesterol levels are frequently observed in familial hypercholesterolemia (FH) and might be associated with functional alterations of HDL particles that may influence their efficaciousness in the reverse cholesterol transport pathway. METHODS AND RESULTS—We evaluated key steps of the reverse cholesterol transport, ie, cellular free cholesterol efflux, cholesteryl ester transfer protein-mediated cholesteryl ester (CE) transfer from HDL to apolipoprotein B–containing lipoproteins, and hepatic HDL-CE uptake, in patients displaying FH (n=12) and in healthy normolipidemic control subjects (n=12). Large HDL2 particles isolated from FH patients displayed a reduced capacity to mediate free cholesterol efflux via both scavenger receptor-BI– and ABCG1–dependent pathways. A significant inverse relationship between scavenger receptor-BI–dependent HDL2 efflux capacity and carotid intima-media thickness (r=−0.473; P=0.0186), as well as between ABCG1-dependent HDL2 efflux capacity and carotid intima-media thickness (r=−0.485; P=0.0212), was detected. We also observed an elevated cholesteryl ester transfer protein-mediated CE transfer from HDL2 and HDL3 particles to low-density lipoprotein and a reduced capacity of HDL particles to deliver CEs to the liver. CONCLUSION—We demonstrated that the centripetal movement of cholesterol from peripheral tissues, including the vessel wall, to feces is defective in FH, thereby emphasizing its atherogenicity.